Letter : Spanish seamen - Spence, W. R.
025a-0036-001 Telegraphic Address: "SEAROVING ALFOLD [LAMB] LONDON" Telephone Nos. DUNSFORD 231 267 280 and 285 National Union of Seamen Registered trade union no. 1493. Approved society certificate no. 128. Affiliated to the Labour Party, International Transportworkers Federation, Trades Union Congress, National Maritime Board (Sailors, Firemen and Catering Panels) EXECUTIVE OFFICERS: General Secretary . W.R Spence, C.B.E. Asst. General Secretary : G. Reed General Treasurer : J.B. Wilson Emergency Address : SACHEL COURT, ALFOLD, Nr. CRANLEIGH, SURREY. Telephone No.: DUNSFOLD 267 Your Ref :— WMC/HVT/FC/620. Our Ref: WRS/A. July 8th 1940. Sir Walter Citrine, K.B.E., Trades Union Congress, Transport House, Smith Square, LONDON, S.W.1. Dear Sir, SPANISH SEAMEN. I am in receipt of your letter of the 5th instant and note full contents re the above. In the circumstances, I have got my Committee to agree to make a grant of £40. towards the expenses incurred and which you are now desirous of clearing up. Cheque is enclosed for this amount, for which kindly let me have your official receipt and oblige. Yours faithfully. W.R. Spence General Secretary. CHK. Sent by Finance Dept. 292/946/25a/36